Implications of COVID-19 pandemic and response approaches in Uganda: Stakeholder perspectives - Moses Ocan; Josephine Bayigga; Adelline Twimukye; Hellen Nansiiro; Daphine Sanger; Mordecai Tayebwa; Boniconsilli Tusiime; Maureen Katusiime; Daniel Kyabayinze; Benon Kwesiga; Henry K. Bosa; Leah Mbabazi; et al. (Journal of Public Health in Africa)
Background: The coronavirus disease 2019 (COVID-19) pandemic significantly impacted health systems worldwide.